Eksplorasi Konsep Lenggono dan Implikasinya dalam Pengasuhan Guna Menumbuhkan Moralitas Anak Berdasarkan Perspektif Keraton Surakarta - A’ida Fayza Fitrianetha; Bani Bacan Hacantya Yudanagara (IAI Nasional Laa Roiba Bogor, 2025)
This study explores the concept of Lenggono and its implications in parenting to foster children's morality from the perspective of the Surakarta Palaces. Using a qualitative case study approach, this research involved officials from the Surakarta Palace who have deep appreciation for Javanese cultural values. Data collection was conducted through a series of three interviews over one month, ensuring participant confidentiality and informed consent. Thematic analysis was employed to identify patterns and themes from the data. The findings highlight the importance of instilling moral education from an early age, emphasizing values such as appreciation for the existence of God, logical straightness of thinking, wisdom, intellectual and emotional intelligence, sympathetic feelings, and non-violence. The Lenggono concept integrates these values, providing a holistic approach to moral education in children, rooted in Javanese traditions. This research contributes to a deeper understanding of cultural practices in moral upbringing and offers practical insights for parents and educators.